Service Quality Improvement and Brand Image of Kulangsu Scenic Spot in Xiamen City, China - Huimin, Bu; Rujithamrongkul, Krisdaporn; Kumboon, Buraporn; Phuvakeereevivat, Ariya (International Journal of Multidisciplinary in Management and Tourism, 2024)
Tourism can generate income for every country around the world that has its own unique points of interest. It will make people interested in traveling in that country. Creating a good impression is therefore an issue that every country should focus on. This article aimed 1)To study personal factors affecting the improvement of service quality at Ku Lang Su Scenic Area Spot in Xiamen City 2) To analyze the direct and indirect factors affecting service quality improvement and the brand image of Kulangsu scenic spot in Xiamen City 3) To construct a model to enhance the customer satisfaction and repeat rate of Kulangsu Scenic Spot in Xiamen city. This study is a mixed methods study. and quantitative studies use convenience sampling. The sample group consisted of 560 tourists who visited the Ku Lang Su scenic spot. The tool used to collect data was a questionnaire survey. Statistical data used in this study include percentage, mean, and standard deviation. The research results were found as follows; 1. Personal information of respondents Most of them are female, 292 people. Most of them have an average age of 18-24 years, 264 people. education is at the bachelor's level, 350 people have a career as a student, and 249 people have an income of less than 2000 yuan. 2. The building of brand image has a strong positive correlation with the satisfaction of tourists to the intention of re-visiting and recommending them. 3. The improvement of service quality has a strong positive correlation with tourists' satisfaction to their intention to visit again. Qualitative research results found that service quality has a positive impact on brand image and customer satisfaction from the perspective of improving service quality and building brand image.